English 3 : english for academic writing - Baraceros, Esther L. (Manila, Philippines : Rex Book Store, 2009)
This book explains, discusses, and makes you do application activities on the foundations of academic writing first, before it deals with the principles of research writing, and before it requires you to come out with an academic or scholarly paper called research or term paper that will an academic or scholarly paper called research or term paper that will prove your mastery of the ins and outs of academic writing.
1. The nature of the writing process -- 2. Expositions -- 3. Argumentation -- 4. Description -- 5. Writing a research paper -- 6. Sample parts of a term paper -- 7. Survey research -- 8. Interview as a tool in survey research -- 9. Sampling strategies -- 10. Questionnaire as a tool in survey research -- 11. The business letter.
Includes bibliographical references and index.
Keywords: TERM PAPER -- SCHOLARLY PAPER -- RESEARCH